2017
DOI: 10.1039/c7ta03117c
|View full text |Cite
|
Sign up to set email alerts
|

A novel catalytic route for hydrogenation–dehydrogenation of 2LiH + MgB2via in situ formed core–shell LixTiO2nanoparticles

Abstract: Aiming to improve the hydrogen storage properties of 2LiH + MgB2 (Li-RHC), the effect of the in situ formed and low cost LixTiO2 is investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 72 publications
5
42
0
Order By: Relevance
“…Investigations into reaction pathways under different temperatures, hydrogen pressures, and stoichiometric compositions were carried out in order to understand the behavior of the Li-RHC and try to optimize its operative conditions. These investigations were focused mainly on the dehydrogenation pathways [33][34][35][36][37][38][39][40]. In 2007, Bösenberg et al [33] first reported the global hydrogenation and dehydrogenation reaction mechanisms of Li-RHC under dynamic conditions.…”
Section: Destabilized Mgh2-2libh4 System: Li-rhcmentioning
confidence: 99%
See 2 more Smart Citations
“…Investigations into reaction pathways under different temperatures, hydrogen pressures, and stoichiometric compositions were carried out in order to understand the behavior of the Li-RHC and try to optimize its operative conditions. These investigations were focused mainly on the dehydrogenation pathways [33][34][35][36][37][38][39][40]. In 2007, Bösenberg et al [33] first reported the global hydrogenation and dehydrogenation reaction mechanisms of Li-RHC under dynamic conditions.…”
Section: Destabilized Mgh2-2libh4 System: Li-rhcmentioning
confidence: 99%
“…It was suggested that this stable compound hinders the full reversibility, and thus it is responsible for the loss of hydrogen capacity [56]. Puszkiel et al [39] and Jepsen et al [40] also studied the dehydrogenation behavior of Li-RHC under equilibrium conditions by PCI curve measurements with different additives, i.e., 2LiH + MgB 2 + 5 mol% TiO 2 [39] and 2LiH + MgB 2 + 5 mol% TiCl 3 [40]. The two-step reaction was also verified in both cases, providing enthalpy values in excellent agreement with the ones for MgH 2 for the higher plateau (~76 kJ mol −1 H 2 [39] and~73 kJ mol −1 H 2 [40]), and enthalpy values in the order of 50-60 kJ mol −1 H 2 for the second plateau ascribed to the dehydrogenation of LiBH 4 and formation of MgB 2 + LiH (~61 kJ mol −1 H 2 [39] and~53 kJ mol −1 H 2 [40]).…”
Section: Destabilized Mgh2-2libh4 System: Li-rhcmentioning
confidence: 99%
See 1 more Smart Citation
“…2LiBH 4 + MgH 2 2LiH + MgB 2 + 4H 2 (52) In the last decade this system has been thoroughly investigated with respect to reaction pathway, temperature and hydrogen pressure boundaries, microstructure, effect of additives on the reaction kinetics, and nanoconfinement [159][160][161][162][163][164][165][166][167][168][169][170][171][172][173].…”
Section: Libhmentioning
confidence: 99%
“…Therefore, the design/synthesis of new additives is mandatory in order to achieve long-lasting absorption/desorption properties. TiO 2 is one of the low-cost additives which enhance the hydrogen storage properties of the 2LiBH 4 + MgH 2 reactive hydride composite (RHC) system [44][45][46] . Puszkiel et al showed that 2LiH + MgB 2 /2LiBH 4 + MgH 2 RHC system doped with core-shell Li x TiO 2 nanoparticles shows improved the kinetic and cycling behaviour 44 .…”
mentioning
confidence: 99%